SYNTHESIS AND PHOTOLYSIS OF SOME TRANSITION METAL COMPLEXES OF SCHIFF BASE LIGAND DERIVED FROM ETHYLENEDIAMINE AND SALICYLICALDEHYDE - WALEED.F. AL-HITY; KAISS .R. IBRAHEEM; MOHAMMED A.AL-HADITHI (مجلة جامعة الانبار للعلوم الصرفة, 2007)
This study deals with the preparation of Schiff- base ligands from the reaction of salicaldehyde with ethylenediamine in the ratios 1:1 of ligand (1) and 1:2 of ligand (2). Their metal complexes with ions Fe (11), Co (11), Ni (11), and Cu (11) were also prepared. The electronic spectrum of all these complexes and the IR spectrum were studied. The ratios of dissociation of these complexes were investigated via radiation by using mercury lamp in the wavelength of 365 nm. It is noticed that these complexes dissociate slowly during the process of radiation.